Decision support systems II - Recent Developments Applied to DSS Network Environments : Euro Working Group Workshop, EWG-DSS 2012, Liverpool, UK, April 12-13, 2012, and Vilnius, Lithuania, July 8-11, 2012, Revised Selected and Extended Papers - Liu, Shaofeng; Delibasic, Boris; Zaraté, Pascale; Dargam, Fatima; Ribeiro, Rita; Hernandez, Jorge E. (Lecture Notes in Business Information Processing, 2013)
This book contains extended and revised versions of a set of selected papers from two workshops organized by the Euro Working Group on Decision Support Systems (EWG-DSS), which were held in Liverpool, UK, and Vilnius, Lithuania, in April and July 2012. From a total of 33 submissions, 9 papers were accepted for publication in this edition after being reviewed by at least three internationally known experts from the EWG-DSS Program Committee and external invited reviewers. The selected papers are representative of the current research activities in the area of decision support systems, focusing on topics such as decision analysis for enterprise systems and non-hierarchical networks, integrated solutions for decision support and knowledge management in distributed environments, decision support system evaluation and analysis through social networks, and e-learning and its application to real environments.